Analyzing the interactome of human CK2β in prostate carcinoma cells reveals HSP70‐1 and Rho guanin nucleotide exchange factor 12 as novel interaction partners. Issue 3 (22nd January 2023) - Nickelsen, Anna; Götz, Claudia; Lenz, Florian; Niefind, Karsten; König, Simone; Jose, Joachim
Abstract: CK2β is the non‐catalytic modulating part of the S/T‐protein kinase CK2. However, the overall function of CK2β is poorly understood. Here, we report on the identification of 38 new interaction partners of the human CK2β from lysates of DU145 prostate cancer cells using photo‐crosslinking and mass spectrometry, whereby HSP70‐1 was identified with high abundance. The KD value of its interaction with CK2β was determined as 0.57 μM by microscale thermophoresis, this being the first time, to our knowledge, that a KD value of CK2β with another protein than CK2α or CK2α′ was quantified. Phosphorylation studies excluded HSP70‐1 as a substrate or activity modulator of CK2, suggesting a CK2 activity independent interaction of HSP70‐1 with CK2β. Co‐immunoprecipitation experiments in three different cancer cell lines confirmed the interaction of HSP70‐1 with CK2β in vivo. A second identified CK2β interaction partner was Rho guanin nucleotide exchange factor 12, indicating an involvement of CK2β in the Rho‐GTPase signal pathway, described here for the first time to our knowledge. This points to a role of CK2β in the interaction network affecting the organization of the cytoskeleton. Abstract : Three CK2β variants with incorporated para ‐azidophenylalanine at different positions were mixed each with DU145 cell lysate and photo‐crosslinking was performed by UV light irradiation. Cross‐linked products were enriched by NiNTA affinity chromatography, digested by trypsin and identified by LC–MS. In total, 43 different proteins coupled to CK2β were found. Binding of HSP70‐1 as one of these was confirmed by microscale thermophoresis and co‐immunoprecipitation experiments in three different cancer cell lines.